UV-induced mutagenesis of human p53 in a vector replicated in Saccharomyces cerevisiae - Moshinsky, Deborah J. (The National Academy of Sciences of the USA, 1997)
Mutation of the p53 tumor suppressor gene is the most common genetic alteration identified to date in human cancers. Similarities of p53 mutations found in human cancers with those induced in experimental systems have been interpreted as evidence supporting a causative role for environmental carcinogens in certain tumor types. We have developed and validated a method for generation of mutation spectra and measurement of mutation frequency directly on human p53 cDNA in a vector following treatment with mutagens and replication in yeast. Mutants that had lost the DNA binding/transcription activation function of p53 were detected by yeast colony color, isolated, and sequenced. UV light was used to characterize and validate the system, and a dose-dependent increase in mutation frequency was seen following exposure of the plasmid to increasing doses of UV, resulting in an 18-fold increase over the spontaneous frequency (3.2 × 10(−4)) at the highest level tested (300 J/m(2)). Sequence analysis of p53 in the mutants revealed that the types of mutations induced were similar to those obtained in previous studies of UV mutagenesis in other model systems, and the types and positions of mutations were also similar to those found in human skin tumors. This experimental system will be useful in further evaluation of the importance of environmental agents as risk factors for cancer.